Conceptual Study of Vishamajwara with Special Reference to Enteric Fever (Typhoid): A Review from Rog Nidan Perspective - Dr. Ujjwal; Dr. (Prof.) Basant Kumar Thakur (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Background: Vishamajwara, a type of Jwara described in Ayurvedic classics, presents with irregular patterns of fever and systemic disturbances. Its Santata form, characterized by continuous fever, exhibits striking similarities with Enteric Fever (Typhoid), a systemic bacterial infection caused by Salmonella typhi. Understanding the Rog Nidan (etiopathogenesis) of Vishamajwara through Ayurvedic literature can provide a holistic and integrative perspective toward managing Typhoid. Aim: To conceptually study Vishamajwara with special reference to Enteric Fever (Typhoid) from the perspective of Rog Nidan. Objectives: To review classical Ayurvedic literature on Vishamajwara, especially Santata Jwara. To analyze the Nidana Panchaka of Vishamajwara. To correlate Vishamajwara with the clinical features of Enteric Fever. To understand the pathological progression (Samprapti) from the Rog Nidan standpoint. To establish a conceptual bridge between Ayurvedic and modern understanding of Typhoid fever. Materials and Methods: A comprehensive review of classical Ayurvedic texts including Charaka Samhita, Sushruta Samhita, Madhava Nidana, and Ashtanga Hridaya was carried out to gather references on Vishamajwara. Contemporary biomedical literature was reviewed to understand the clinical features and pathophysiology of Enteric Fever. Comparative analysis was done to identify overlaps and differences in etiopathogenesis. Results: Santata Vishamajwara is described as a persistent, often low-grade fever associated with Dhatukshaya, Agni-mandya, and Srotorodha. Its Samprapti aligns closely with the pathogenesis of Typhoid involving systemic infection, endotoxemia, and GI disturbances. Nidana factors like Dushta Ahara, Jala, and Ajirna are common in both conditions. The Ayurvedic perspective offers insights into early diagnosis, understanding chronicity, and rational Chikitsa planning based on Dosha Dushya Sammurchana. Conclusion: A thorough understanding of Santata Vishamajwara through the lens of Rog Nidan enables an integrative diagnostic model for managing Enteric Fever. Ayurvedic principles of diagnosis based on Nidana Panchaka can support early intervention and individualized treatment strategies. Further clinical correlation is needed to establish evidence-based Ayurvedic management protocols.